2010
DOI: 10.1071/an09035
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic and phenotypic parameters for production, haematological and gastrointestinal nematode-associated traits in Australian Angora goats

Abstract: Genetic parameters for liveweight (LWT), greasy fleece weight (GFW), mean fibre diameter (MFD), standard deviation of MFD (MFD-s.d.), mean fibre curvature (CURVE) percentage of medullated (%MED) and kemp (%KEMP) fibres, faecal worm egg count (WEC), packed cell volume (PCV), mean corpuscular volume (MCV) mean corpuscular haemoglobin content (MCHC), circulating anti-nematode IgG (IgG) and counts of circulating eosinophils (EOS), lymphocytes (LYM), neutrophils (NEU), basophils (BASO) and monocytes (MONO) up to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
5
6
2
Order By: Relevance
“…Correlation analyses of the data showed that live weight was positively correlated with eosinophil counts. This result is in agreement with Bolormaa et al (2010) and Olayemi et al (2011) where eosinophil counts were positively associated with the live weight of Australian Angora and Cashmere goats naturally infected and followed by challenge infections with T. colubriformis. They suggested that such positive correlations between live weight and eosinophil counts may indicate resistance to infection rather than of the infection itself.…”
Section: Correlations and Regressions Between Parasite-associated Measupporting
confidence: 90%
See 4 more Smart Citations
“…Correlation analyses of the data showed that live weight was positively correlated with eosinophil counts. This result is in agreement with Bolormaa et al (2010) and Olayemi et al (2011) where eosinophil counts were positively associated with the live weight of Australian Angora and Cashmere goats naturally infected and followed by challenge infections with T. colubriformis. They suggested that such positive correlations between live weight and eosinophil counts may indicate resistance to infection rather than of the infection itself.…”
Section: Correlations and Regressions Between Parasite-associated Measupporting
confidence: 90%
“…In this study MCV, MCH and RDW values dropped especially in the younger groups of goats for both sexes similar to the finding of Ameen et al (2006). MCHC values also dropped in this study in agreement with Bolormaa et al (2010). However, in this study the values of MCV and MCH were dropped but not significantly lower compared to the MCHC and RDW throughout study period.…”
Section: Erythrocytessupporting
confidence: 83%
See 3 more Smart Citations